Recent advances in the improvement of carboxymethyl cellulose-based edible films - Yildirim-Yalcin, Meral; Tornuk, Fatih; Toker, Omer Said (ELSEVIER SCIENCE LONDON, 2022)
Background: Cellulose has attracted the interest of the industry since it is the most abundant natural poly-saccharide obtained from natural sources such as wood, cotton and food wastes, agricultural residues, cereals brans, fruit peels. Usage of CMC and its derivatives in edible film production with desired characteristics is very important for recycling of food wastes and sustainability and biodegradability.Scope and approach: This review covers the recent developments in CMC based edible films. Production pro-cedures and quality properties of CMC based edible films and usage of advantages/disadvantages of edible films containing CMC and its derivatives in food applications are discussed. Ingredients used to improve quality characteristics of the CMC based composite/blend films and their effects on quality characteristics are also investigated. Usage possibilities of bioactive ingredients to improve antioxidant and antimicrobial properties of CMC based films are also summarized.Key findings and conclusion: As CMC based film does not have required quality properties CMC modified with chemical methods can provide better characteristics. Mechanical and other quality parameters of CMC based films can be improved by addition of several ingredients. CMC films with antioxidant and antimicrobial prop-erties have great potential for reducing food wastes and environmental pollution, improving food quality, safety and security.
Keywords: Packaging; Edible film; Carboxymethyl cellulose; Coating; Shelf life; WAX EMULSION FILMS; ACTIVE PACKAGING FILM; ANTIMICROBIAL PROPERTIES; ESSENTIAL OIL; PHYSICOCHEMICAL PROPERTIES; POTASSIUM SORBATE; CANDELILLA WAX; CROSS-LINKING; ASCORBIC-ACID; COATINGS; Food Science & Technology